The complete guide to successful event planning - Kilkenny, Shannon (Florida: Atlantic, Inc., 2006)
Contents: Scope. How and when to use this guide. Benefits to the reader. Intende audience. What should we call it, Using checklist and timelines.
Keywords: Eventos Especiales